The Influence of Academic Resilience And Student Well-Being on Smartphone Addiction - Fitri Khairani Nasution; Nurussakinah Daulay (Universitas Pahlawan Tuanku Tambusai, 2022)
Various problems experienced by students at school such as the many academic pressures that are difficult to deal with will trigger stress on students and divert stress by playing smartphones excessively, so that it will have a negative impact on their lives. To prevent smartphone addiction, self-protection factors are needed, namely academic resilience and student psychological well-being. The purpose of the study was to determine the effect of academic resilience and student well-being on smartphone addiction at MTs Nurul Islam Indonesia. The subjects of this study amounted to 198 students. The type of research used is a quantitative approach with multiple linear regression analysis techniques. The results of the study showed that there was a significant effect of academic resilience on smartphone addiction of t(-6,448), p = 0.00 (p<0.05), and significantly with a value of 0.000 <0.05 and a large influence of 21.5% on smartphones. addictions. However, there was no significant effect of student well-being on smartphone addiction t(1.208), p = 0.0229 (p>0.05).